Más allá de las fronteras: emergencia de la ciudadanía como un derecho humano (2020)
Regardless of nationality, people are subjects of enforceable rights in the framework of international relations and States are obliged to account in their actions for certain guarantees enforceable through the supranational organizations that together make up the basic structure of the international political community, with a public space that absorbs the state public space; that is, the public space of citizenship, today goes beyond the context of the state and is configured from a space of supranational order. In this context, citizenship as a human right emerges, which constitutes our object of analysis based on the precepts of the Inter-American Court of Human Rights, which express the reconfiguration of the political community, the idea of Human Rights as an international public reason, as support for the emergence of citizens based on human rights.